Survey of Physical Fitness Level for Students with Mental Retardation on Extraordinary Elementary School in Donggala Regency (Journal of Physical Education and Sports, 2018)
The purpose of the study was to determine the level of physical fitness of students with mental retardation on an extraordinary elementary school in Donggala Regency. This study is evaluation research using descriptive research methods. The sample of this study was all students with mental retardation on an extraordinary elementary school in Donggala Regency. The sampling technique in this study was purposive sampling. The sample in this study amounted to 10 students consisting of 6 male students and 4 female students. Retrieving data using the Indonesian Physical Fitness Test (TKJI). The results of the study used descriptive percentages with descriptions as follows: excellent categories = 0%, good categories = 0%, moderate categories = 20%, less categories = 60%, and very few categories = 20%. From the results of data analysis shows that the level of physical fitness of students with mental retardation on an extraordinary elementary school in Donggala Regency is less category. Based on the results of data analysis, sports and health physical education teachers need to design learning that is suitable for the growth and development of students so that they can improve their physical fitness.